Book on eService-Learning Posits Goals of Service-Learning Pedagogy and Technology's Role in Achieving Them - Sarah Stanlick (The University of Alabama, 2022)
Review of the book: Jean Strait and Katherine J. Nordyke (Eds.), eService-Learning: Creating Experiential Learning and Civic Engagement Through Online and Hybrid Courses. Sterling, VA: Stylus Publishing, 2015, 182 pages. ISBN 978-1-62036-064-4